A construção da confiança na América do Sul e os mecanismos de transparência militar - Silva, Diego Lopes da [UNESP] (2014)
The research aims to analyze the South American Register of Military Expenditure, established under the South American Defense Council (CDS in its portuguese acronym). We sought to identify in the methodological and political structure of the initiative, traces of past regional experiences. We defend the hypothesis that the existence of bilateral initiatives of transparency in military affairs, prior to the establishment of the mechanism in the CDS, were driving conditions for the succesful establishment of the Register. For its verification, we investigated the historical process which culminated in the creation of the mechanism in two levels of analysis: the hemispheric and bilateral. The intention is to study not only the event but also the process, ensuring context to the analysis. We searched, in investigating other transparency mechanisms, parameters that could help in the methodological analysis of the South American Registry. Thus, considering the South American historical lines and the analytical parameters acquired in the study of other initiatives, we analyzed the South American Register of Military Expenditure, seeking to observe in what manner and to what extent its establisment contributed to the development of South American confidence